2021
DOI: 10.1002/adma.202106248
|View full text |Cite
|
Sign up to set email alerts
|

Spiderweb Nanomechanical Resonators via Bayesian Optimization: Inspired by Nature and Guided by Machine Learning

Abstract: temperature conditions where thermomechanical noise can dominate. The degree of mechanical isolation is characterized by a resonator's mechanical quality factor, Q m . Typically, Q m is defined as the ratio of energy stored in a resonator over the energy dissipated over one cycle of oscillation. Inversely, mechanical quality factors can indicate the dissipation of mechanical noise into a resonator from ambient environments. For mechanical sensors, a resonator's isolation from ambient thermal noise can greatly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…Furthermore, phononic bandgap engineering is impractical at low frequencies due to the large device sizes required (tens of millimeters for the 100 kHz range). Contemporaneous work such as perimeter modes 21 and “spider-web” resonators 22 have demonstrated low dissipation at low frequencies, but not for the fundamental mode of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phononic bandgap engineering is impractical at low frequencies due to the large device sizes required (tens of millimeters for the 100 kHz range). Contemporaneous work such as perimeter modes 21 and “spider-web” resonators 22 have demonstrated low dissipation at low frequencies, but not for the fundamental mode of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize this trade-off, we fabricated resonators with different devices and geometries which led to a wide range of quality factors up to 10 9 at room temperature [24]. Hence, we acquired the spectrum of each resonator and found that, above Q m = 10 7 , our read-out protocol cannot detect the change of the mechanical displacement x 2 as function of temperature, due to the low linewidth Γ m .…”
Section: Fabrication Of Suspended 2d Square Membranesmentioning
confidence: 99%
“…Along with micro-and nano-structuration, the miniaturization of whole mechanical resonators has been pushed to the micrometric scale; among the others, a wide investigation has interested nanometer-thick, micrometer-wide membranes [6][7][8] . Thanks to their large quality factors 6,9,10 and extreme aspect ratio, these kinds of device have been used as a standard platform for classical and quantum effects in optomechanics 9,11 and for light 12 , pressure 13 , mass 14 and other sensing applications 7,15 . The mechanical membranes are an ideal platform for hosting photonic metasurfaces, which can be introduced by periodically patterning a portion of the device.…”
mentioning
confidence: 99%
“…where σ and ε are the stress and strain tensor, respectively. σ ex is an extra contribution possibly given by initial strain, as in the case of strongly pre-stressed materials such as Si 3 N 4 10,32,33 . The constituent materials of the membrane, namely Si 3 N 4 and Au, are fully isotropic and can be described by the Young's modulus E and Poisson's ratio ν, which are embedded inside the compliance tensor S. The material density ρ completes the set of parameters needed for the simulation.…”
mentioning
confidence: 99%